CD4-Targeted T Cells Rapidly Induce Remissions in Mice with T Cell Lymphoma. (28th March 2021) - Cheng, Jie; Chen, Guanghua; Lv, Hui; XU, Liangjing; LIU, Huiwen; Chen, Tianping; Qu, Lijun; Wang, Jian; Cheng, Lemei; Hu, Shaoyan; Wang, Yi
Abstract : Objective . To explore the immune cell therapy for T cell lymphoma, we developed CD4-specific chimeric antigen receptor- (CAR-) engineered T cells (CD4CART), and the cytotoxic effects of CD4CART cells were determined in vitro and in vivo. Methods . CD4CART cells were obtained by transduction of lentiviral vector encoding a single-chain antibody fragment (scFv) specific for CD4 antigen, costimulatory factor CD28 fragment, and intracellular signal transduction domain of CD3 fragments. Control T cells were obtained by transduction of reporter lentiviral vector. The cytotoxicity, tumor growth, and survival rate of mice with T cell lymphoma were analyzed after adoptive T cell transfer in vivo. Results . CD4CART cells had potent cytotoxic activity against CD4+ T1301 tumor T cells in a concentration-dependent manner. In addition, adoptive CD4CART cell transfer significantly suppressed tumor growth and improved animal survival with T cell lymphoma, compared to the mice who received control T cells and PBS. Conclusion . CD4CART cells have potent cytotoxic effects on T cell lymphoma. The study provided an experimental basis for CD4CART-mediated therapy of T cell lymphoma.